LEGAL PROTECTION OF CUSTOMERS/INVESTORS FROM FRAUD CRIMES COMMITTED BY INDIVIDUALS AND NON-BANK FINANCIAL INSTITUTIONS - Wicaksono, Hadi; Pratiwi, Siswantari; Saefulloh (JILPR Journal Indonesia Law and Policy Review, 2024)
Illegal investment activities are carried out by collecting funds from the wider community by deviating or even avoiding banking regulations, which are activities that use public facilities to carry out their business activities. Thus, it is necessary to look at the authority that the Financial Services Authority has in providing protection for the public against Illegal Investment activities. The practice of moral hazard in Illegal Investment activities occurs because of the weak supervision system of financial institutions. Problem Formulation What are the factors that cause the crime of illegal investment fraud? What is the legal protection for customers of non-bank financial institutions who carry out collection activities without permission from Bank Indonesia and the OJK? The research method used is normative juridical, the results of this research are factors that cause the occurrence of criminal acts of illegal investment fraud, such as a lack of public awareness of the financial sector, especially legal investments, and the bad luck of those who seek high profits while ignoring the risks and legal protection for institutional customers. Non-Bank Finance Carrying Out Collection Activities Without Permission from Bank Indonesia and OJK Finance is a mechanism for legal protection of customers, namely by pursuing civil and general criminal charges.